Brief comments on three existing approaches for managing neonates at risk of early-onset sepsis - E. Vaccina; A. Luglio; M. Ceccoli; M. Lecis; F. Leone; T. Zini; G. Toni; L. Lugli; L. Lucaccioni; L. Iughetti; A. Berardi (BMC, 2021)
Abstract Background Growing concerns regarding the adverse effects of antibiotics during the first days of life and the marked reduction in the incidence of early-onset sepsis (EOS) are changing the clinical practice for managing neonates at risk of EOS. Strategies avoiding unnecessary antibiotics while promoting mother-infant bonding and breastfeeding deserve to be considered. Main body We compare strategies for managing newborns at risk of EOS recommended by the American Academy of Pediatrics, which are among the most followed recommendations worldwide. Currently three different approaches are suggested in asymptomatic full-term or late preterm neonates: i) the conventional management, based on standard perinatal risk factors for EOS alone, ii) the neonatal sepsis calculator, a multivariate risk assessment based on individualized, quantitative risk estimates (relying on maternal risk factors for EOS) combined with physical examination findings at birth and in the following hours and iii) an approach entirely based on newborn clinical condition (serial clinical observation) during the first 48 h of life. We discuss advantages and limitations of these approaches, by analyzing studies supporting each strategy. Approximately 40% of infants who develop EOS cannot be identified on the basis of maternal RFs or laboratory tests, therefore close monitoring of the asymptomatic but at-risk infant remains crucial. A key question is to know what proportion of babies with mild, unspecific symptoms at birth can be managed safely without giving antibiotics. Conclusions Both neonatal sepsis calculator and serial clinical observation may miss cases of EOS, and clinical vigilance for all neonates is essential There is a need to assess which symptoms at birth are more predictive of EOS, and therefore require immediate interventions, or symptoms that can be carefully reevaluated without necessarily treat immediately the neonate with antibiotics. Studies comparing strategies for managing neonates are recommended.